Rapid Maize Leaf and Immature Ear Responses to UV-B Radiation - Casati, Paula; Morrow, Darren J.; Fernandes, John; Walbot, Virginia (Frontiers in Plant Science, 2011)
Because of their sessile lifestyle, plants have evolved adaptations to environmental factors, including UV-B present in solar radiation. To gain a better understanding of the initial events in UV-B acclimation, we have analyzed a 10min to 1h time course of transcriptome responses in irradiated and shielded leaves, and immature maize ears to unravel the systemic physiological and developmental responses in exposed and shielded organs. After 10 min of UV-B exposure, 262 transcripts are changed by at least 2-fold in irradiated leaves, and this number doubles after 1h. Indicative of the rapid modulation of transcription, 130 transcripts are only changed after 10 min. This is true not only in irradiated leaves, but also in shielded tissues. After 10 min of exposure, the overlap in transcriptome changes in irradiated and shielded organs is significant; however, after 30 min of UV-B, there are only 2 transcripts showing similar UV-B regulation between the three organs; 35 are similarly regulated in both IL and SL. Therefore, at longer irradiation times, there is more specificity of responses, and these are organ-specific. We suggest that early signaling in different tissues may be elicited by common signaling pathways, while at longer exposure times responses become more specific. To identify metabolites as possible signaling molecules, we looked for compounds that increased within 5-90 min in both irradiated and shielded leaves, to explain the kinetics of profound transcript changes within 1h. We found that myoinositol is one such candidate metabolite; and we also demonstrate that if 0.1mM myoinositol is applied to leaves of greenhouse maize, some metabolites that are changed by UV-B are also changed similarly by the chemical treatment. Therefore, this metabolite can partially mimic UV irradiation.